Evidence brief: Supporting the evidence-based use of cannabis for chronic pain in Canada - Moat, KA; Bain, T; Bhuiya, AR; DeMaio, P; Alam, S; Lavis, JN (My University, 2023)
A synthesis of what is known, based on the best available global and local research evidence about the problem(s) related to supporting the evidence-based e use of cannabis for chronic pain in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This evidence brief was prepared to inform a stakeholder dialogue.
Keywords: evidence-based; cannabis; chronic pain; Canada